Rice Stripe Virus Coat Protein-Mediated Virus Resistance Is Associated With RNA Silencing in Arabidopsis - Sun, Feng; Hu, Peng; Wang, Wei; Lan, Ying; Du, Linlin; Zhou, Yijun; Zhou, Tong (Frontiers in Microbiology, 2020)
Rice stripe virus (RSV) causes rice stripe disease, which is one of the most serious rice diseases in eastern Asian countries. It has been shown that overexpression of RSV coat protein (CP) in rice plants enhances resistance against virus infection. However, the detailed mechanism underlying RSV CP-mediated virus resistance remains to be determined. In this study, we show that both translatable and nontranslatable RSV CP transgenic Arabidopsis plants exhibited immunity to virus infection. By using deep sequencing analysis, transgene-derived small interfering RNAs (t-siRNAs) from nontranslatable CP transgenic plants and virus-derived small interfering RNAs (vsiRNAs) mapping in the CP region from RSV-infected wild-type plants showed similar sequence distribution patterns, except for a significant increase in the abundance of t-siRNA reads compared with that of CP-derived vsiRNAs. To further test the correlation of t-siRNAs with RSV immunity, we developed RSV CP transgenic Arabidopsis plants in an siRNA-deficient dcl2/3/4 mutant background, and these CP transgenic plants showed the same sensitivity to RSV infection as nontransgenic plants. Together, our data indicate that the expression of RSV CP protein from a transgene is not a prerequisite for virus resistance and RSV CP-mediated resistance is mostly associated with the RNA silencing mechanism in Arabidopsis plants.